2022
DOI: 10.1111/nyas.14812
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation through conductive scaffolds for cardiomyocyte tissue engineering: Systematic review and narrative synthesis

Abstract: Electrical conductivity is of great significance to cardiac tissue engineering and permits the use of electrical stimulation in mimicking cardiac pacing. The development of biomaterials for tissue engineering can incorporate physical properties that are uncommon to standard cell culture and can facilitate improved cardiomyocyte function. In this review, the PICOT question asks, "How has the application of external electrical stimulation in conductive scaffolds for tissue engineering affected cardiomyocyte beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 72 publications
0
1
0
Order By: Relevance
“…[21][22][23] Previous literature has reported that electrical stimulation in conductive bioscaffolds can support cardiac cell viability, help promote maturation, and facilitate and increase gap junction protein expression. [24][25][26] Many of the biomaterials used in field stimulation showed low spatiotemporal resolutions for cellular stimulation, which could limit the extent of mechanistic studies involving cardiac electrical signaling. As such, light-based approaches that could increase the resolution of stimulation, most of them being based on synthetic materials if not relying on optogenetics, offer a minimally invasive way of doing so.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Previous literature has reported that electrical stimulation in conductive bioscaffolds can support cardiac cell viability, help promote maturation, and facilitate and increase gap junction protein expression. [24][25][26] Many of the biomaterials used in field stimulation showed low spatiotemporal resolutions for cellular stimulation, which could limit the extent of mechanistic studies involving cardiac electrical signaling. As such, light-based approaches that could increase the resolution of stimulation, most of them being based on synthetic materials if not relying on optogenetics, offer a minimally invasive way of doing so.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Previous literature has reported that electrical stimulation in conductive bioscaffolds can support cardiac cell viability, help promote maturation, and facilitate and increase in gap junction protein expression. [21][22][23] Many of the biomaterials used in field stimulation showed low spatiotemporal resolutions for cellular stimulation, which could limit the extent of mechanistic studies involving cardiac electrical signaling. As such, light-based approaches that could increase the resolution of stimulation, most of them being based on synthetic materials if not relying in optogenetics, offer a minimally invasive way of doing so.…”
Section: Introductionmentioning
confidence: 99%